2014
DOI: 10.1103/physreve.90.022711
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical mechanism of antifreeze proteins to prevent ice growth

Abstract: The fascinating ability of algae, insects and fishes to survive at temperatures below normal freezing is realized by antifreeze proteins (AFPs). These are surface-active molecules and interact with the diffusive water/ice interface thus preventing complete solidification. We propose a new dynamical mechanism on how these proteins inhibit the freezing of water. We apply a Ginzburg-Landau type approach to describe the phase separation in the two-component system (ice, AFP). The free energy density involves two f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Note that some previous studies (28,40) reported the possibility that IBPs may decrease the free energies of ice-water interfaces, resulting in faster growth kinetics and more pronounced morphological instability. In this study, the effect of fcIBP11 on the free energy of ice-water interfaces remains uncertain.…”
Section: Discussionmentioning
confidence: 90%
“…Note that some previous studies (28,40) reported the possibility that IBPs may decrease the free energies of ice-water interfaces, resulting in faster growth kinetics and more pronounced morphological instability. In this study, the effect of fcIBP11 on the free energy of ice-water interfaces remains uncertain.…”
Section: Discussionmentioning
confidence: 90%
“…A similar effect was reported by DeLuca et al [13], who reported that an increment in the AFP activity is observed when the type III AFP is linked to other proteins and thus its size is increased. From a theoretical point of view, several models have been proposed relating thermal hysteresis activity with the portion of ice surface occupied by AFPs [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. These approaches stimulate the researchers to develop more refined theoretical solutions for the adsorption thermodynamics of complex adsorbates (in this case, proteins of different sizes and shapes).…”
Section: Introductionmentioning
confidence: 99%
“…This would suggest that AFPs avoid the growth of a post-critical ice nucleus rather than impeding the formation of an ice nucleus. Nevertheless, despite a growing body of the literature on ice-binding proteins, [6][7][8][9]11,12,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] a complete study on the antifreeze effect of the AFP concentration on the ice growth is still missing.…”
Section: Introductionmentioning
confidence: 99%